Recobrimento com fertilizante fosfatado de sementes de soja e sua eficiência na germinação, crescimento, produtividade e na disponibilidade de fósforo no solo - Castaldo , João Henrique (2021)
The search for better operational efficiency in crops led Brazilian soybean producers to adopt the use of seeders without fertilization in the sowing furrow, carrying out this operation via broadcast at surface, which can bring difficulties in supply and absorption of elements that have reduced mobility in the soil, such as phosphorus (P), requiring new techniques to position the phosphate fertilizer closer to the seed, such as covering the seeds with solid phosphate fertilizers. The objective of this work was to evaluate the covering of soybean seeds with solid phosphate fertilizer in different granulometries and doses, regarding the visual quality of the covering and the effects that this technique results in the physiological quality of the seeds, in addition to the use of the covered seeds in successive soybean crops in soils with different levels of P. It was evaluated the in a laboratory experiment, the visual quality of the coating, the percentage of seed germination, the emergence and growth of seedlings when subjected to four fertilizer grain sizes (Mesh-Tyler 35, 70, 115 and 270) combined with four doses of fertilizer applied in the coating (6, 12, 24 and 48% of the grain’s mass in fertilizer), The covering of soybean seeds with solid phosphate fertilizer reduced the percentage of germination and emergence of soybean seeds as finer grain sizes and higher doses of fertilizer were used, however, the quality of the coating was better when higher doses with thinner fertilizer were used. In sequence, three experiments were carried out in a greenhouse to assess the use of soybean seeds covered with solid fertilizer in two years of cultivation, evaluating plant growth and soybean productivity and phosphorus content in the soil. The use of covered seeds increased the P content in the soil, resulting in a higher growth of soybean plants that produced more grains than when phosphate fertilization was carried out on the surface. The covering of soybean seeds is an alternative in the positioning of phosphate fertilizer in the sowing furrow with the use of seed-only sowers.